Molecular Modeling, Washington University - Washington University (Saint Louis, Mo.); Barry, C. David (1970)
Silent video of a three-dimensional lactate dehydrogenase molecule imaged and manipulated using software developed at Washington University at least in part by C. David Barry. This footage, created by pointing a camera at the computer's graphic display while a user manipulates the digital model via a keyboard or other hardware, shows the main chain and helices, pleated sheets, sub-unit interactions, super secondary structures, coenzyme binding, and conformational changes. This version has been edited to remove the last six minutes of footage, which are a repeat of the first six minutes.
Keywords: Lactate dehydrogenase; Computer simulation; Molecular structure--Computer simulation; Molecular structure--Computer programs; Molecular structure